Zoonotic Foodborne Infections in a Tertiary Healthcare Setting: Clinical and Epidemiological Aspects of Campylobacter and Salmonella Infection in Northern Portugal in 2010–2020 - Maria Inês Matos; Rafael Rocha; João Pinto; André Guimarães; Rita Lino; Maria Helena Rocha; Marta Patacho; Raquel Duro; Lurdes Santos; Jorge Almeida (Microbiology Research)
This study aimed to describe the epidemiology, clinical presentation, and management of Campylobacter sp. and Salmonella sp. infections in a tertiary hospital in Northern Portugal (2010–2020) and identify factors associated with reporting, invasive disease, and hospitalization. A retrospective review included patients with Campylobacter sp. (2015–2020) or Salmonella sp. infections (2010–2020). Reported cases were cross-referenced with the National Epidemiological Surveillance System. A total of 742 patients were included: 342 with Campylobacter sp., 392 with non-typhoidal Salmonella (NTS), and 15 with typhoidal Salmonella (TS). Immunosuppression was present in 16.7% of cases. NTS infections were invasive in 21.4% of cases, compared to 4.0% for Campylobacter. Macrolide resistance in Campylobacter reached 10%, particularly in C. coli, while multidrug resistance (MDR) was observed in 37.8% of NTS isolates. Immunocompromised patients accounted for over 70% of relapses in Campylobacter disease. Reporting rates were low: 32.8% for NTS, 30.6% for Campylobacter, and 14.3% for TS. Reporting was associated with male sex, no immunosuppression, hospitalization, and non-MDR organisms. In conclusion, immunocompromised patients face higher risks of invasive and relapsing disease. High rates of MDR in NTS limit treatment options. Underreporting remains significant, underscoring the need for improved awareness and reporting to inform public health strategies.